2021
DOI: 10.1172/jci150398
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory cytokines TNF-α and IL-17 enhance the efficacy of cystic fibrosis transmembrane conductance regulator modulators

Abstract: Without CFTR-mediated HCO3secretion, airway epithelia of newborns with cystic fibrosis (CF) produce an abnormally acidic airway surface liquid (ASL), and the decreased pH impairs respiratory host defenses. However, within a few months of birth, ASL pH increases to match that in non-CF airways. Although the physiological basis for the increase is unknown, this timecourse matches the development of inflammation in CF airways. To learn whether inflammation alters CF ASL pH, we treated CF epithelia with TNFα and I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
54
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(69 citation statements)
references
References 76 publications
12
54
3
Order By: Relevance
“…Recently, Rehman et al reported that inflammation enhances the response to CFTR modulators in vitro and in vivo [60]. The in vitro studies employed TNFα and IL-17 as inflammatory stimuli [60], and their findings are in agreement with our previous in vitro studies demonstrating that the CF airway inflammatory milieu enhances the efficacy of CFTR modulators [32,58].…”
Section: Airway Inflammation Enhances Cftr Modulator Therapy-improved Lung Function In Vivosupporting
confidence: 77%
See 4 more Smart Citations
“…Recently, Rehman et al reported that inflammation enhances the response to CFTR modulators in vitro and in vivo [60]. The in vitro studies employed TNFα and IL-17 as inflammatory stimuli [60], and their findings are in agreement with our previous in vitro studies demonstrating that the CF airway inflammatory milieu enhances the efficacy of CFTR modulators [32,58].…”
Section: Airway Inflammation Enhances Cftr Modulator Therapy-improved Lung Function In Vivosupporting
confidence: 77%
“…As discussed above, although VX-770 destabilizes rescued F508del [59,63], inflammation can overcome the detrimental effects of chronic exposure to ivacaftor [32]. Hence, we speculate that through a mechanism involving inflammationdependent CFTR stabilization, the efficacy of chronic VX-770 treatment is improved in CF patients, resulting in increases in forced expiratory volume in 1 s (FEV 1 ), as observed by Rehman et al [60].…”
Section: Airway Inflammation Enhances Cftr Modulator Therapy-improved Lung Function In Vivosupporting
confidence: 65%
See 3 more Smart Citations